Novel diagnostic approaches to intrauterine neoplasm in fertile age: sonography and hysteroscopy. Issue 5 (1st October 2021) - Della Corte, Luigi; Vitale, Salvatore Giovanni; Foreste, Virginia; Riemma, Gaetano; Ferrari, Federico; Noventa, Marco; Liberto, Aldo; De Franciscis, Pasquale; Tesarik, Jan
Abstract: Endometrial carcinoma (EC) is the most common gynecological malignancy in the world. It is mostly detected in postmenopausal women, but it can also occur in women of fertile age who need fertility-sparing therapy. An early diagnosis is the main objective for the correct management of these patients, making it possible to use a fertility-sparing treatment approach without exposing the patients to the risk of cancer progression. In this review, we discuss the role of sonography and hysteroscopy in the detection of intrauterine neoplasm in women of childbearing age.